2018
DOI: 10.1017/qua.2017.103
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of Late Pleistocene loess profiles at Remizovka (Kazakhstan) indicates the significance of topography in evaluating terrestrial paleoclimate records

Abstract: We report on a loess-paleosol sequence (LPS) near Remizovka, located in the northern Tian Shan piedmont of southeastern Kazakhstan. This site represents a key record for Late Pleistocene climatic fluctuations at the intersection of major northern hemisphere climate subsystems. This paper develops a synthesized dataset of previous conflicting studies at Remizovka by characterizing their (paleo)topographic context, which had remained previously overlooked. Digital elevation models, satellite images, and archival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…Loess cover in Kazakhstan is different from that of other regions in arid central Asia (see Figure 6), especially that encountered in China (Fitzsimmons et al, 2018;Sprafke et al, 2018). Unlike on the Chinese loess plateau (and also in Tajikistan), the thickness of the strata is influenced by the underlying topography (Sprafke et al, 2018) so that it is difficult to target a particular time period by field-walking near predetermined strata (e.g., see paleosols, see Zhu et al, 2018).…”
Section: Discussion: Possible Biases In the Archaeological Recordmentioning
confidence: 97%
See 1 more Smart Citation
“…Loess cover in Kazakhstan is different from that of other regions in arid central Asia (see Figure 6), especially that encountered in China (Fitzsimmons et al, 2018;Sprafke et al, 2018). Unlike on the Chinese loess plateau (and also in Tajikistan), the thickness of the strata is influenced by the underlying topography (Sprafke et al, 2018) so that it is difficult to target a particular time period by field-walking near predetermined strata (e.g., see paleosols, see Zhu et al, 2018).…”
Section: Discussion: Possible Biases In the Archaeological Recordmentioning
confidence: 97%
“…Alternating loess-paleosol (LP) sequences showcase climatic changes from relatively dry and cold periods (represented by the loess) and relatively humid and warm periods (represented by soil formation). Recent research in Kazakhstan has shown that this information can be combined with that drawn from human occupations to create a relatively nuanced picture of human-environment interactions (Machalett et al, 2008;Feng et al, 2011;Fitzsimmons et al, 2017;Sprafke et al, 2018). Moreover, sites appear to often be located in similar landscape locations, often at the beginning of alluvial fans created by intramontane rivers.…”
Section: Loessmentioning
confidence: 99%
“…Previous quantitative approaches to local stratigraphy include magnetic susceptibility in a high resolution (Hambach, 2010) and a characterisation of GH5 to GH28 by horizon‐wise description, geochemistry and grain‐size data (Terhorst et al ., 2014). Here, we aim to compare sediment columns from different areas of the excavated area surrounding the preserved occupation layer AH4.4/4.3, in order to improve our 3D understanding of sedimentary processes caused by potential palaeotopographic influences (Sprafke et al ., 2018). Grain size and colour are the basic parameters of loess–palaeosol sequences (LPS) that allow robust stratigraphic subdivisions and the reconstruction of LPS‐forming processes.…”
Section: Study Layoutmentioning
confidence: 99%
“…The accumulation and preservation of deposited dust are highly dependent on local landforms (Nottebaum et al, ; Sprafke et al, ; Stevens & Lu, ). Erosion is often an important factor, so that DMAR (dust mass accumulation rates) <DF (deposition flux); however, loess deposits on escarpments facing the wind direction may experience enhanced dust deposition (Bowen & Lindley, ; Mason et al, ), resulting in DMAR = DF.…”
Section: Introductionmentioning
confidence: 99%